(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Slavery in our current era has reappeared, but in different forms and patterns, and in all countries of the world, as commercial companies are exploiting people due to poor economic conditions. Which makes people more exploited for others, Today, new forms of the modern slave system have emerged, such as serfdom, forced labor, debt bondage, and the current paradigm of slavery is the exploitation of migrant workers, especially in Europe and the Arab Gulf States. And employers of migrant workers gain a great deal of control over their jobs by offering to take care of their wages. This is a practice that the employer usually justifies by ensuring that the revenue is not lost, or that they invest it to give the worker some additional gains. And because of the low status of the migrant worker, he is often unable to refuse the employer’s offer or not aware that caution warrants rejection of that offer. After the employer collects wages for several months, the worker becomes in a vulnerable position if he wishes to leave and must therefore bear a large amount of abuse in order to collect his revenues. Sometimes this transgression includes physical abuse or rape and denial of taking their wages, and although international standards on slavery do not specifically provide that denial of taking or not paying wages to workers is a form of slavery, it is clear that such a practice violates human rights. The United Nations and the International Labor Organization have concluded several agreements in an effort to confront and solve the problem.